Abordagem do tema meio ambiente no currículo paulista anos finais: uma análise a partir de fundamentos da educação ambiental crítico-transformadora via tema gerador - Bevilacqua, Luís Fernando (Universidade Federal de São Carlos, 2025)
This study examines Critical-Transformative Environmental Education through the Generative Theme approach (EACT-TG), as proposed by Torres (2010), investigating its theoretical foundations and its application in the analysis of the “Currículo Paulista” (São Paulo, 2019) for the final years of elementary education. The research begins by reviewing the main curriculum theories, categorized by Silva (2016) into Traditional, Critical, and Post-Critical approaches, and enriched by contributions from other relevant scholars. The focus then shifts to the concept of the environment, discussing socially constructed representations (Naturalist, Anthropocentric, and Globalizing) as defined by Reigota (2010), along with a brief history of the environmental movement and Environmental Education (EE) in Brazil. The study also explores the major trends in EE (Conservationist, Pragmatic, and Critical), systematized by Layrargues and Lima (2014), emphasizing the principles of Critical Environmental Education (CEE) and its connection to Paulo Freire’s Pedagogy of Liberation. A brief biography of Freire is presented, highlighting his contributions to education, such as dialogue, problem-posing, and generative themes, which underpin the EACT-TG approach. The methodology is qualitative, with an emphasis on bibliographic research and document analysis, understanding research as a reflective and dialogical process influenced by and influencing social life. Finally, the study conducts an in-depth analysis of how the theme of the environment is addressed in the “Currículo Paulista” for the final years of elementary education, using the core principles of EACT-TG (Dialogue and Problematization toward Awareness) as analytical parameters. The theoretical framework confirms that EACT-TG aims not only at environmental awareness but also at transforming the sociocultural and material relations of concrete reality, thereby providing a foundation for data analysis. The comparative analysis between the “Currículo Paulista” (São Paulo, 2019) and the principles of EACT-TG indicates that the curriculum reveals more divergences than alignments, limiting its emancipatory potential. Although the curriculum acknowledges the cross-cutting nature of environmental issues, it addresses the theme superficially, without incorporating students’ lived experiences or questioning the structural causes of environmental crises. Its emphasis on individual actions and prescriptive nature restricts teacher autonomy and distances the curriculum from a critical and transformative educational approach, as envisioned by Freirean principles.
Approach to the environment theme in the São Paulo curriculum for final years: an analysis from the fundamentals of critical-transformative environmental education through a generating theme
Enfoque del tema medio ambiente en el currículo paulista años finales: un análisis a partir de los fundamentos de la educación ambiental crítico-transformadora a través del tema generador
Keywords: Meio ambiente; Currículo; Paulo Freire; Educação ambiental crítico-transformadora.; Environment; Curriculum; Critical-transformative environmental education; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO